(untitled) (مجلة إحالات, 2026)
The Covid-19 pandemic forced teachers and students to leave university for a long time. To this end, it was necessary to think of a solution that would allow them to continue their studies and distance learning was the only solution to be able to ensure the continuity of teaching and learning. Our article is a reflection on hybrid education through the Moodle platform among students of the department of letters and French language of the University of Saida. We will try to evaluate the representation of this mode of teaching.